2022
DOI: 10.3390/met12122110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrolytic Copper Foil Roughness on Lithium-Ion Battery Performance

Abstract: Improving the interfacial properties between the electrode materials and current collectors plays a significant role in lithium-ion batteries. Here, four kinds of electrolytic copper foils with roughness (Rz) values of 1.2, 1.5, 2.2, and 2.8 μm were prepared via an electropolishing technique. Reducing the roughness of the electrolytic copper foil can effectively improve the wettability of the anode slurry. The electrolytic copper foil with a roughness value of 1.2 μm shows the best coating uniformity of the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Lithium-ion batteries are currently among the most used in electric passenger cars [77] , being the anode current collector of these batteries mainly electrolytic copper foil. In relation to this, it has been reported that reducing the roughness of electrolytic copper foil might be a feasible route to improve the performance of LIBs [74] .…”
Section: Copper In Lithium-ion Batteries (Libs)mentioning
confidence: 97%
See 1 more Smart Citation
“…Lithium-ion batteries are currently among the most used in electric passenger cars [77] , being the anode current collector of these batteries mainly electrolytic copper foil. In relation to this, it has been reported that reducing the roughness of electrolytic copper foil might be a feasible route to improve the performance of LIBs [74] .…”
Section: Copper In Lithium-ion Batteries (Libs)mentioning
confidence: 97%
“…E-waste had a different soil metal profile (Cu > Pb > Zn > Cr > Ni > Co > As > Cd > Hg) from that of the non-e-waste soils, being growth and reproduction of A. nilotica significantly inhibited when exposed to e-waste soils. On the other hand, in China Zhang et al [74] used the life cycle assessment (LCA) method to analyze the global environmental impact of copper-based mixed waste recovery. To evaluate the differences in the environmental impact associated with recycling processes, the results were compared with those obtained for primary copper production.…”
Section: Potential Sources Of Human Exposure To Copper: Metallurgy/sm...mentioning
confidence: 99%
“…Nevertheless, the application of a primer layer can be advantageous, as it creates a defined surface condition for the application of the slurry and the quality can be increased considerably. In addition to the possibility of using a primer to improve adhesion, the mechanical modification of the foil surface was also suggested by Babaiee et al and Zhang et al [28,29]. It was found that increased roughness improves adhesion, but partially impairs the electrochemical properties.…”
Section: Challenges In Industrial Battery Cell Manufacturingmentioning
confidence: 99%
“…6 As the anodic current collector in lithium-ion batteries, it is imperative to further enhance the mechanical properties of ECFs to meet the high requirements for manufacturing efficiency and consistency in power batteries while achieving ultrathin design. 7,8 The stress formula, σ = F/S, reveals that as the ECF becomes thinner (which means the smaller cross-sectional area S), the external force required for its rupture will decrease. The prevailing thickness of ECF used in current lithium-ion batteries has been reduced to 6 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Electrolytic copper foils (ECFs) are an important raw material for electronic devices, mainly used in lithium-ion batteries and printed circuit boards. With the current electronic products moving toward miniaturization, lightweight design, and enhanced functionality, higher demands are being placed on the performance of ECFs . As the anodic current collector in lithium-ion batteries, it is imperative to further enhance the mechanical properties of ECFs to meet the high requirements for manufacturing efficiency and consistency in power batteries while achieving ultrathin design. , The stress formula, σ = F / S , reveals that as the ECF becomes thinner (which means the smaller cross-sectional area S ), the external force required for its rupture will decrease. The prevailing thickness of ECF used in current lithium-ion batteries has been reduced to 6 μm.…”
Section: Introductionmentioning
confidence: 99%